Values of Religion and Organizational Culture: Study of Phenomenology in The Context of Prophetic Ontology and Adaptive Culture - Umiarso, Umiarso (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study examines the concept of appreciating Islamic values in fostering an organizational culture at the Miftahul Ulum Suren Islamic Boarding School (PMUS) Jember, especially in implementing and integrating Islamic values. This study uses adaptive culture theory with qualitative research methods and phenomenological types. The research participants were three Kiai and ustadz in Islamic boarding schools. The interview technique was used to dig up complete data. Data analysis was carried out by data reduction procedures, presentation, and interpretation. This study finds that the institutional culture of pesantren is born out of the theological and philosophical values of the Kiai, which are lived by giving examples (role models), guidance, teaching, training, or using the experiences of the pesantren residents themselves. This culture has implications for the achievements of the pesantren, including the achievement of the prophetic tasks of the pesantren.